2017
DOI: 10.5194/isprs-archives-xlii-2-w7-1547-2017
|View full text |Cite
|
Sign up to set email alerts
|

Local and General Monitoring of Forni Glacier (Italian Alps) Using Multi-Platform Structure-From-Motion Photogrammetry

Abstract: ABSTRACT:Experts from the University of Milan have been investigating Forni Glacier in the Italian alps for decades, resulting in the archive of a cumbersome mass of observed data. While the analysis of archive maps, medium resolution satellite images and DEM's may provide an overview of the long-term processes, the application of close-range sensing techniques offers the unprecedented opportunity to operate a 4D reconstruction of the glacier geometry at both global and local levels. In the latest years the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Such kind of targets (about 7-10 per campaign) could be clearly recognized in images from drone, but not in terrestrial photos. After trying solutions based on total station measurements of another set of GCPs for terrestrial blocks (see Scaioni et al, 2017) or trying to directly determine the position of camera stations using GNSS as proposed in Forlani et al (2015), we abandoned these approaches because too much involved to handle in the glacier environment. Thus, the georeferencing of each "terrestrial" point cloud has been done by the co-registration to the contemporary point cloud obtained from drone photogrammetry.…”
Section: Sfm From Terrestrial and Drone Platformsmentioning
confidence: 99%
“…Such kind of targets (about 7-10 per campaign) could be clearly recognized in images from drone, but not in terrestrial photos. After trying solutions based on total station measurements of another set of GCPs for terrestrial blocks (see Scaioni et al, 2017) or trying to directly determine the position of camera stations using GNSS as proposed in Forlani et al (2015), we abandoned these approaches because too much involved to handle in the glacier environment. Thus, the georeferencing of each "terrestrial" point cloud has been done by the co-registration to the contemporary point cloud obtained from drone photogrammetry.…”
Section: Sfm From Terrestrial and Drone Platformsmentioning
confidence: 99%
“…Given a suitable geodetic reference, multi-platforms surveys may be integrated to obtain full 3D models which completely depict geomorphic objects under different point of views. A review on the application of photogrammetry to the study of Alpine glaciers can be found in Fugazza et al (2017) and Scaioni et al (2017). This paper would like to describe the acquisition and processing steps of two data sets aimed at mapping risk on the surface of Forni Glacier.…”
Section: Modelling the Glacier Surface Using Photogrammetrymentioning
confidence: 99%
“…Since 2007, several high-resolution DSMs have been derived to witness the dynamic evolution of the terminus tongue of Forni Glacier. While a more detailed description can be found in Scaioni et al (2017), here we limit to give a short mention.…”
Section: Available Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. In Scaioni et al (2017a) a discussion is reported whether is better to acquire more images with shorter baselines, or less images with longer baselines and a more regular geometry. The proposed solution is to capture a larger number of images with shorter baselines, since the number of points in the final point cloud is proportional to the number of employed image; 2.…”
Section: Terrestrial Blocksmentioning
confidence: 99%